Pharmacokinetics-Guided Dosing of 5-Fluorouracil for Precision Cancer Treatment: A Focus on Colorectal Carcinoma - Chen, Yanming; S. Yee, Nelson (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2016)
5-Fluorouracil (5-FU) is a principal chemotherapeutic agent for treatment of a variety of malignant diseases. The standard method for dosing of 5-FU has been based on body surface area. Significant variation of plasma levels of 5-FU among individuals has been shown to influence the clinical outcomes. Accumulating data suggest that area under the concentration versus time curve (AUC)-based dosing of 5-FU improves the clinical efficacy and safety profile. In this article, we reviewed the pharmacokinetics (PK) of 5-FU and discussed the studies of PK-guided dose adjustment of 5-FU in colorectal cancer. In recent studies, the value of PK monitoring and modifying of 5-FU plasma level based on AUC has been investigated. As demonstrated by these data, AUC-based dosing is associated with improved treatment responses and reduced toxicity. Commercially available immunoassay is available to accomplish PK-based dosing of 5-FU, and that is increasingly utilized in routine clinical practice. In conclusion, monitoring of plasma levels of 5-FU is a promising method to improve the outcome of patients with colorectal cancer in terms of clinical efficacy and toxicity. Large randomized trials are warranted to further verify this hypothesis and generalize the use of PK-guided dosing of 5-FU for precision cancer treatment.
Keywords: 5-fluorouracil